2016
DOI: 10.15171/jrip.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in patients with diabetic foot infection; does antibiotherapy affect it?

Abstract: Introduction: Antibiotic treatment (antibiotherapy) of diabetic foot ulcers has been proven to have toxic effect on renal function. Objectives: This study aimed to evaluate renal function in patients with diabetic foot infection. Patients and Methods: This cross-sectional retrospective study was performed on 142 patients with diabetic foot ulcers hospitalized in Shahid Yahyanejad hospital of Babol during 2013. After referring to profile of the patients, they were assigned to participate in two groups: group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Akbari et al in a study investigated the effect of anti-biotherapy on renal function. They evaluated 142 patients and found that GFR contributed to renal function and it was reduced in children treated by antibiotics (14), which is similar to the current findings. Also, Wolf et al in their study found that impaired renal function was higher in infections of diabetic foot (15).…”
Section: Discussionsupporting
confidence: 86%
“…Akbari et al in a study investigated the effect of anti-biotherapy on renal function. They evaluated 142 patients and found that GFR contributed to renal function and it was reduced in children treated by antibiotics (14), which is similar to the current findings. Also, Wolf et al in their study found that impaired renal function was higher in infections of diabetic foot (15).…”
Section: Discussionsupporting
confidence: 86%
“…Systemic antibiotic therapy is known to have toxic effects on renal function with significant reduction in estimated glomerular filtration rate (eGFR) [ 32 ]. Four (10%) patients from this case review were identified to develop acute kidney injury (AKI) ( Table 3 and Table 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several medicinal plants such as Galega officinalis, in addition to producing positive effects on glucose homeostasis in diabetic patients, have found application in preventing and treating hypertension, cardiovascular disease, and kidney injury [13,58,59,60]. In addition to producing hypoglycemic effects, numerous plants have been demonstrated to be effective against the wide range of diabetic complications (Table 1).…”
Section: Insulin Resistance Reductionmentioning
confidence: 99%